Effect of Phosphorus Fertilization on its Transformations in Different Soils under Dry Direct-Seeded Rice - Yadvinder-Singh and Bijay-Singh, R.K. Gupta, Navpreet Rathore (Journal of the Indian Society of Soil Science, 2016)
Greenhouse experiment on dry direct-seeded rice (DSR) was conducted to study the effect of three levels of fertilizer P (0, 6.5, 13 mg kg-1 soil) application on the changes in P fractions in ten different soils varying in Olsen-P and texture. The concentration of Ca-P fraction increased significantly with the application of P fertilizer over no-P treatment at maximum tillering stage. The increase in Ca-P fraction at flowering was significant only at 13 mg P kg-1 over no P application. The values of Fe-P and Al-P fractions did not differ significantly irrespective of the initial Olsen-P concentration or P application. The concentration of Olsen-P in soils increased significantly with the application of P fertilizer over no-P control at both maximum tillering and flowering stages of DSR.